Analisis Dampak Pengamanan Manajemen File Mahasiswa Fakultas Ilmu Komputer Di Universitas Bhayangkara Jakarta Raya - Agus Setiawan; Arrizal Bintang Ramadhan; Farid Ilham; Ihsan Ahmad Fauzan (Journal of Informatic and Information Security, 2024)
This study was conducted to measure the level of compliance with file security policies among students of Bhayangkara University, Greater Jakarta. This study focused on the system and student data protection. The author investigated the factors that influence students' privacy policies. The author conducted research to determine the value of compliance with data security. The author conducted statistical data processing based on questionnaires filled out by students. The findings of this study provide an indication of the level of data security compliance among students in universities and the factors that influence it. The author tries to correlate compliance with factors that can affect the level of compliance in the implementation of data protection systems.